Conformational dynamics of dynamin-like MxA revealed by single-molecule FRET - Yang Chen; Lei Zhang; Laura Graf; Bing Yu; Yue Liu; Georg Kochs; Yongfang Zhao; Song Gao (Nature Communications, 2017)
MxA (myxovirus resistance protein A) is a viral restriction factor whose activity depends on self-assembly into polymeric rings and helical filaments. Here the authors reveal the conformational movements involved in generating torque within polymeric MxA molecules and the dynamic conformational changes that occur upon GTP loading and hydrolysis.